2022
DOI: 10.1039/d1cp04993c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transition metal cations on the local structure and lithium transport in disordered rock-salt oxides

Abstract: Lithium-excess oxides Li1.2Ti0.4Mn0.4O2 and Li1.3Nb0.3Mn0.4O2 with a disordered rock-salt structure and Mn3+/Mn4+ as a redox couple were compared to analyze the effect of different d0 metal ions on the local structure and Li+ ion migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Previously, the formation of ONb6 and OMn1Nb5 octahedra, more stable than Mn-rich ones, was confirmed in DRX oxide Li1.3Nb0.3Mn0.4O2 by computational methods [8]. On the other hand, using geometricaltopological method (bond-valence site energy modeling, BVSE), and density functional theory (DFT) calculations, we demonstrated that Mn ions form MnO6 clusters, which are preferably linked in dense layers in Li1.3Nb0.3Mn0.4O2, and negatively affects lithium diffusion [9]. The formation of Mn clusters was also confirmed by EPR and NMR spectroscopy [9][10][11].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previously, the formation of ONb6 and OMn1Nb5 octahedra, more stable than Mn-rich ones, was confirmed in DRX oxide Li1.3Nb0.3Mn0.4O2 by computational methods [8]. On the other hand, using geometricaltopological method (bond-valence site energy modeling, BVSE), and density functional theory (DFT) calculations, we demonstrated that Mn ions form MnO6 clusters, which are preferably linked in dense layers in Li1.3Nb0.3Mn0.4O2, and negatively affects lithium diffusion [9]. The formation of Mn clusters was also confirmed by EPR and NMR spectroscopy [9][10][11].…”
Section: Introductionmentioning
confidence: 68%
“…Earlier, it was found that the Li1.3Nb0.3Mn0.4O2 oxide has a tendency to form the Mn 3+ -O-Mn 4+ clusters [9]. On the other hand, the authors [10] revealed ferromagnetic interactions in Li1.2Ti0.4Mn0.4O2 oxide during cycling.…”
Section: Local Orderingmentioning
confidence: 96%
“…For example, the current finding of Li–Ti and Ni–Ni clustering preference in LTNNO is in line with the previous theoretical investigations, where prominent Li–Ti and Ni–Ni clusterings were found in a DRX material Li 1.0 Ti 0.5 Ni 0.5 O 2 . Regarding the Nb 5+ cations, Semykina et al pointed out that, in a Li 1.3 Nb 0.3 Mn 0.4 O 2 system, the presence of Nb 5+ tends to prompt the segregation of Mn 3+ cations …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2d, the composition of TM elements shows a monotone change as the TM number in the cation cluster , the presence of Nb 5+ tends to prompt the segregation of Mn 3+ cations. 52 In the view of thermodynamics, the formation of SRO in DRX material is driven by the preferred phase segregation at the low temperature, thus resembling the structural features of its ground state. The existence of such structurally ordered domains strongly affects Li + mobility within DRX material.…”
Section: Structural Feature Statistics and Sro Existence In Ltnnomentioning
confidence: 99%
“…[8][9][10][11][12] Several transition metals such as Mn, Ti, V, and Cr have been utilized to synthesize DRXs with capacities of up to 300 mA h g −1 . [13][14][15][16][17] Transition metal cation mixing, 11,18 shortrange ordered structure analysis, [19][20][21][22] and the Li + migration mechanism [23][24][25][26] are highly researched to activate the high capacity and improve the rate performance of DRXs. Recently, Konuma et al reported a "near dimensionally invariable" material Li 8/7 Ti 2/7 V 4/7 O 2 , which was encapsulated in Li 6 PS 5 Clbased ASSBs using a PEEK mold and achieved a capacity of 300 mA h g −1 at a high operating pressure of 200 MPa and a current of 0.2 C (60 mA g −1 ).…”
Section: Introductionmentioning
confidence: 99%